2015
DOI: 10.1108/bjm-03-2014-0039
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncrasy, heterogeneity and evolution of managerial styles in contemporary Russia

Abstract: Purpose – The purpose of this paper is to examine managerial styles of Russian managers in the context of institutional and economic environment of contemporary Russia. Design/methodology/approach – The study is based on a sample of 482 line and middle managers covering eight geographic regions, 14 industries and 80 organizations in Russia. Findings – Employing factor and cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 60 publications
0
21
1
Order By: Relevance
“…Lastly, we note that our analyses found the role of control variables such as gender, age and hierarchical position to be insignificant in predicting how the three leadership styles influence employee work engagement. Our study indicates that although these variables might affect what leadership orientations Russian employees have, as previous research has suggested (Astakhova et al, 2010;Balabanova et al, 2015), they do not influence how Russian employees react to different leadership styles with work engagement behaviors. It suggests the predominant role of employees' implicit leadership theories in determining their reactions to different leadership behaviors over employees' gender, age and hierarchical position.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Lastly, we note that our analyses found the role of control variables such as gender, age and hierarchical position to be insignificant in predicting how the three leadership styles influence employee work engagement. Our study indicates that although these variables might affect what leadership orientations Russian employees have, as previous research has suggested (Astakhova et al, 2010;Balabanova et al, 2015), they do not influence how Russian employees react to different leadership styles with work engagement behaviors. It suggests the predominant role of employees' implicit leadership theories in determining their reactions to different leadership behaviors over employees' gender, age and hierarchical position.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, also followers’ perceptions and expectations of leaders change and potentially become more heterogeneous (Epitropaki, Sy, Martin, Tram-Quon, & Topakas, 2013; Ling, Chai, & Fang, 2000; Offermann & Coats, 2018). In support, specifically in the Russian context, the focal context of this article, a range of different managerial styles has been found to coexist and be effective in organizations (Balabanova, Efendiev, Ehrnrooth, & Koveshnikov, 2015; Balabanova, Rebrov, & Koveshnikov, 2018). Furthermore, several researchers have claimed that since the 1990s the traditional control-oriented leadership style has been gradually replaced or complemented in Russia by more Westernized ones, such as, authoritative (e.g., Fey, Adaeva, & Vitkovskaia, 2001; Kets de Vries, 2000; McCarthy, Puffer, & Darda, 2010).…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations